I Brazilian guideline on hypertension in dialysis of the Brazilian Society of Nephrology - Cibele Isaac Saad Rodrigues; Sebastião Rodrigues Ferreira-Filho; Ana Flávia de Souza Moura; Carlos Eduardo Poli-de-Figueiredo; Dirceu Reis da Silva; Fernanda Salomão Gorayeb Polacchini; Fernando Antônio de Almeida; Maria Eliete Pinheiro; Rodrigo Bezerra; Rogério Baumgratz de Paula; Aldo José Peixoto; Ana Elizabeth Prado Lima Figueiredo; et al. (Brazilian Journal of Nephrology)
Abstract Hypertension in dialysis patients (HTND) has a high prevalence, affecting at least 80% or more of patients, and its management in the nephrology practice is heterogeneous and often empirical. Knowing how to define, understand the pathophysiology, diagnose, monitor and treat with lifestyle changes, and adjust antihypertensive drugs to achieve the recommended blood pressure (BP) target - to reduce morbidity and mortality - requires specific knowledge and approaches within the contexts of hemodialysis (HD) and peritoneal dialysis (PD). This document is the first guideline of the Brazilian Society of Nephrology, developed by the departments of Hypertension and Dialysis. It aims to guide physicians who provide care in dialysis centers on how to manage patients with HTND, in a comprehensive and individualized manner, based on the critical appraisal of the best available scientific evidence. When such evidence is scarce or unavailable, the opinion of specialists should be recommended. The different topics covered include HTND definition (pre-HD BP ≥ 140/90 mmHg and post-HD BP ≥ 130/80 mmHg), epidemiology, and pathophysiology; diagnosis of HTND preferably with BP measurements outside the dialysis setting (BP ≥ 130/80 mmHg); complementary assessment; blood pressure targets; non-pharmacological treatment; use of the most appropriate antihypertensive medications; special situations; and complications of HTND, predominantly cardiovascular ones.